BYPASS SURGERY IN PATIENTS WITH COMBINED ATHEROSCLEROTIC LESIONS OF COMMON AND INTERNAL CAROTID ARTERY - N. A. Yaitskiy; A. Ya. Bedrov; D. V. Maslevtsov; A. A. Vrabiy; A. A. Moiseev; Yu. A. Pugachenko (Вестник хирургии имени И.И. Грекова)
An analysis of data of carotid angiographies was made in 146 patients with chronic cerebrovascular disease. Combined lesions of the common and internal carotid artery with clinical signs were revealed in 2 (1,4%) patients. A crossed extraanatomic bypass from the left common carotid artery to the right internal carotid artery was performed in one patient. The orthotopic common-internal autovenous bypass on the right side was carried out for another patient. According to obtained results, the authors suggested that the orthotopic or extraanatomic common-internal carotid artery bypasses could be applied in case of impossibility of endovascular intervention, when patients had the combined atherosclerotic lesions of common carotid and internal carotid artery.